Tlingit potlatch dancer in costume, Sitka, Alaska, ca. 1900 - Hegg, Eric A., 1867-1948
Man in beaded and embroidered headdress and neckpiece, over a fur blanket, ca. 1898-1902. He has painted his face, wears a nose-ring and holds a carved staff. Caption on image: Potlatch dancer, Alaska Caption on border: Sitka Indian. Potlatch dancer.